2019
DOI: 10.17656/sdj.10098
|View full text |Cite
|
Sign up to set email alerts
|

Management of Gummy Smile by Surgical and Non- Surgical Techniques: A Clinical Comparative Study

Abstract: Objective: Gummy smile (GS) also referred to an excessive gingival display (EGD). it’s an aesthetic disorder that can be managed by a variety of procedures include; modified lip reposition surgery (MLRS) and botulinum toxin type-A injection (BTX-A). This study aimed to evaluate and compare the effect of treatment of GS by surgical technique (MLRS) and non-surgical technique (BTX-A injection) 1 and 4 months after treatment.  Methods: The study was conducted from November 2018 to November 2019. Forty adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Two RCTs [ 23 , 24 ] one clinical trial (with unknown type) [ 25 ], two quasiexperimental studies without control group [ 12 , 26 ], seven case series [ 27 33 ], and 26 case reports [ 10 , 34 – 58 ] met the inclusion criteria. For the one RCT with two arms of LRS and botulinum toxin type-A injection, we included the LRS arm in our study [ 24 ]. Characteristics of the included studies are reported in Table S3 (a, b, c, and d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two RCTs [ 23 , 24 ] one clinical trial (with unknown type) [ 25 ], two quasiexperimental studies without control group [ 12 , 26 ], seven case series [ 27 33 ], and 26 case reports [ 10 , 34 – 58 ] met the inclusion criteria. For the one RCT with two arms of LRS and botulinum toxin type-A injection, we included the LRS arm in our study [ 24 ]. Characteristics of the included studies are reported in Table S3 (a, b, c, and d).…”
Section: Resultsmentioning
confidence: 99%
“…We contacted the authors of 36 studies in an effort to obtain additional information. Twelve authors responded to our emails [ 12 , 23 , 24 , 28 , 32 , 39 41 , 52 54 , 57 ]. Obtained data from five authors was added to the tables [ 28 , 32 , 39 , 41 , 52 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation